The developing microbiome : lessons from early life - Claud, Erika C. (Academic Press, imprint of Elsevier, 2020)
The Developing Microbiome: Lessons from Early Life focuses on the establishment of the microbiome in early life, exposing it as a key mediator of diseases and health throughout the lifecycle. The content presents a comprehensive view of the status of the field and draws real-world correlations to health and disease states. It collates the significant research being done in the pediatric microbiome research space and bridges the knowledge gap showing the factors that impact health and disease states throughout the lifecycle. Finally, it offers knowledge on how the microbiome is and can be manipulated to promote change. This is a perfect reference for both researchers and clinical scientists who are interested in the role of the infant microbiome in health and disease, as well as gastroenterologists and pediatricians looking to affect change in their patients.